New response patterns in point-to-origin tasks depending on stimulus type and response mode - Riecke, Bernhard E.; Stepanova, Ekaterina R.; Kitson, Alexandra (International Meeting of the Psychonomic Society, 2016)
We used an online point-to-origin tasks to investigate potential influences of stimuli type (video vs. textual) and response format (textual vs. pictogram multiple choice answers). Using an online survey tool, participants (N=124) either saw a simulated 2-segment outbound path (two straight segments with a 60° or 90° turn in-between) or a textual description thereof. At the path end, participants chose one out of four options that best describes the direction to the starting point. Options were either textual (e.g., back left) or pictorial using a schematic top-down view (hypothesized to trigger a more embodied response). As expected, we observed both turner (participants responding as if successfully updating heading and movement) and non-turner responses (responding as if failing to update heading). Unexpectedly, we observed two additional response patterns, which we termed spinner (responded as if they turned 180° at the end of the trajectory before pointing) and non-mover (responded as if pointing from the origin of motion to the end location). The embodied response condition yielded more non-turners than textual condition, as predicted by the increased reference frame conflict between to-be-imagined and physical orientation. Surprisingly, text-text conditions elicited a significant number of non-movers (p<0.001), suggesting interference between text comprehension and imaginary navigation; while in video-pictogram conditions we observed many spinner responses (p<0.01). Our data suggests that presentation and respond modes reveal additional strategies used in point-to-origin tasks, which cannot be explained through the failure to update the heading solely. Further research on the origins and distribution of different strategies is required.
Keywords: Riecke; Riecke_2016; alex-kitson; bernhard-riecke; katerina-stepanova; point-to-orig; point-to-origin; talkWithoutPaper